2016
DOI: 10.1002/app.44223
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvent on postcuring in free radical photopolymerization

Abstract: During free radical photopolymerization, with an increasing degree of conversion, the viscosity increased and vitrification occurred. The unreacted double bonds had difficulty diffusing to the reactive site in the vitrifying polymer. However, the free radicals generated in the vitrifying matrix could survive for a long time. Thus, the postcuring process occurred. In this study, free radical photopolymerization kinetics of methacrylate with or without solvent was investigated by real‐time FTIR, which was combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The steepest curing and the highest DBC% were received for the neat resin. After 2 s of irradiation, 67% of the double bonds were converted, followed by the highest 78% DBC% reached after 8 s. Herein, achieved curing time characteristics were considerably enhanced compared to the curing of poly(methyl methacrylate) and 1,6-hexanediol dimethacrylate formulations discussed by Zhang et al [ 42 ], where after 5, 10, and 15 s of UV-light irradiation, the DBC% reached 18, 55, and 72%, respectively. Steyrer et al showed that the additional post-curing at elevating temperatures of the UV-light irradiation had increased DBC% by 2-fold [ 41 ].…”
Section: Resultsmentioning
confidence: 69%
“…The steepest curing and the highest DBC% were received for the neat resin. After 2 s of irradiation, 67% of the double bonds were converted, followed by the highest 78% DBC% reached after 8 s. Herein, achieved curing time characteristics were considerably enhanced compared to the curing of poly(methyl methacrylate) and 1,6-hexanediol dimethacrylate formulations discussed by Zhang et al [ 42 ], where after 5, 10, and 15 s of UV-light irradiation, the DBC% reached 18, 55, and 72%, respectively. Steyrer et al showed that the additional post-curing at elevating temperatures of the UV-light irradiation had increased DBC% by 2-fold [ 41 ].…”
Section: Resultsmentioning
confidence: 69%